Fiduciary Systems Assessment of the Oaxaca Water and Sanitation Sector Modernization Project - World Bank (Washington, DC, 2014)
Public Financial Management of the Mexican Federal administration relies on open and orderly Financial Management (FM) systems based on a strong legal framework, policies, and procedures for execution of public expenditures. These FM country systems are partially replicated in the State of Oaxaca and, in particular, in the Secretariat of Finance (Secretaria de Finanzas, SEFIN), which will be coordinating the overall implementation of the Program, and in the executing entities, the State Water Commission (Comision Estatal de Agua, CEA) and the Oaxaca Metropolitan Area Water Utility (SAPAO), which will be responsible for carrying out technical activities under the Program. Although SEFIN has limited experience in managing Bank-financed operations, and CEA and SAPAO have no such experience, the overall conclusion of the FM assessment is that SEFIN, CEA and SAPAO1 have suitable financial management arrangements, which include the key elements for an adequate implementation of the Program, such as: (i) a formal process of budget planning and execution based on comprehensive legal and normative frameworks; (ii) the approval of the State Expenditures Budget on an annual basis by the State Legislature; (iii) an integrated budgeting and accounting system (SINPRES), which allows for the management and control of financial resources; (iv) organizational structures with adequate segregation of duties, documented in the appropriate Functions and Organizational Manuals, and (v) experienced staff.